Dysmetabolism, Diabetes and Clinical Outcomes in Patients Cured of Chronic Hepatitis C: A Real‐Life Cohort Study. Issue 4 (22nd November 2021) - Valenti, Luca; Pelusi, Serena; Aghemo, Alessio; Gritti, Sara; Pasulo, Luisa; Bianco, Cristiana; Iegri, Claudia; Cologni, Giuliana; Degasperi, Elisabetta; D'Ambrosio, Roberta; del Poggio, Paolo; Soria, Alessandro; et al.
Abstract : The aim of this study was to examine the impact of features of dysmetabolism on liver disease severity, evolution, and clinical outcomes in a real‐life cohort of patients treated with direct acting antivirals for chronic hepatitis C virus (HCV) infection. To this end, we considered 7, 007 patients treated between 2014 and 2018, 65.3% with advanced fibrosis, of whom 97.7% achieved viral eradication (NAVIGATORE‐Lombardia registry). In a subset (n = 748), liver stiffness measurement (LSM) was available at baseline and follow‐up. Higher body mass index (BMI; odds ratio [OR] 1.06 per kg/m 2, 1.03‐1.09) and diabetes (OR 2.01 [1.65‐2.46]) were independently associated with advanced fibrosis at baseline, whereas statin use was protective (OR 0.46 [0.35‐0.60]; P  < 0.0001 for all). The impact of BMI was greater in those without diabetes ( P  = 0.003). Diabetes was independently associated with less pronounced LSM improvement after viral eradication ( P  = 0.001) and in patients with advanced fibrosis was an independent predictor of the most frequent clinical events, namely de novo hepatocellular carcinoma (HCC; hazard ratio [HR] 2.09 [1.20‐3.63]; P  = 0.009) and cardiovascular events (HR 2.73 [1.16‐6.43]; P  = 0.021). Metformin showed a protective association against HCC (HR 0.32 [0.11‐0.96]; P  = 0.043), which was confirmed after adjustment for propensity score ( P  = 0.038). Diabetes diagnosis further refined HCC prediction in patients with compensated advanced chronic liver disease at high baseline risk ( P  = 0.024). Conclusion: Metabolic comorbidities were associated with advanced liver fibrosis at baseline, whereas statins were protective. In patients with advanced fibrosis, diabetes increased the risk of de novo HCC and of cardiovascular events. Optimization of metabolic comorbidities treatment by a multi‐disciplinary management approach may improve cardiovascular and possibly liver‐related outcomes.